Preparation method for adhesively bonding 7xxx aluminum alloys and related products

Laser exfoliation of intermetallic particles on 7xxx aluminum alloys, combined with functionalization, addresses bonding challenges by creating a clean surface for strong adhesive bonds in automotive applications.

JP7617879B2Active Publication Date: 2025-01-20ARCONIC TECHNOLOGIES LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022150392
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-06-28
Filing Date
2022-09-21
Publication Date
2025-01-20
Estimated Expiration
2038-06-27

AI Technical Summary

Technical Problem

Adhesive bonding of 7xxx aluminum alloys is challenging due to the presence of surface oxide layers and intermetallic particles, which interfere with effective adhesion to themselves and other materials, particularly in automotive applications.

Method used

A method involving laser exfoliation of intermetallic particles and surface oxide layers on 7xxx aluminum alloys to create exfoliation voids, maintaining the alloy's composition and grain structure, followed by functionalization with phosphorus-containing organic acids to enhance adhesive bonding.

Benefits of technology

The method improves adhesive bonding performance by creating a clean surface with controlled exfoliation pits, allowing for strong and durable bonds without copper redeposition, suitable for automotive and aerospace manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617879000002
    Figure 0007617879000002
  • Figure 0007617879000003
    Figure 0007617879000003
  • Figure 0007617879000004
    Figure 0007617879000004
Patent Text Reader

Abstract

Generally, the present disclosure relates to methods for preparing magnesium-containing aluminum alloys (eg, containing 0.2-6 wt. % Mg) for adhesive bonding, and to products made by such methods. A method for preparing a magnesium-containing aluminum alloy product for adhesive bonding includes a magnesium-containing aluminum alloy product including a substrate and a surface oxide layer overlying the substrate. The magnesium-containing aluminum alloy product also includes intermetallic particles proximate to at least the surface oxide layer. The method also includes ablating at least a portion of the intermetallic particles with an energy source, and no melting of the substrate of the magnesium-containing aluminum alloy product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The 7xxx aluminum alloys are aluminum alloys that have zinc and magnesium as their major alloying components in addition to aluminum. [Background technology]

[0002] It would be useful to promote adhesive bonding of 7xxx aluminum alloys to themselves and to other materials (e.g., for automotive applications). Summary of the Invention [Means for solving the problem]

[0003] Generally, the present disclosure relates to methods for preparing magnesium-containing aluminum alloys (e.g., containing 0.2-6 wt.% Mg) for adhesive bonding, and products made by such methods. To illustrate the inventive aspects of the method, 7xxx aluminum alloys (e.g., AlZnMg or AlZnMgCu alloys) are generally used below. However, any suitable magnesium-containing aluminum alloy may be used in the method.

[0004] In one approach, and now referring to Figures 1-5, a method (300) may include receiving (302) a 7xxx aluminum alloy product (100) having a 7xxx aluminum alloy substrate (106) with a surface oxide layer (102). The surface oxide layer (102) may include an aluminum oxide (e.g., AlO) sublayer (108) and a magnesium oxide (e.g., MgO) sublayer (110). The as-received surface oxide layer (102) typically has an as-received thickness (104) (typically 5-60 nm thick) depending on the temper. Products shipped in W or T tempers may have a thicker as-received thickness (e.g., about 20-60 nm) and F temper products may have a thinner as-received oxide layer thickness (e.g., about 5-20 nm). Although the as-received surface oxide layer (102) is illustrated as being generally uniform, the as-received surface oxide layer typically has a non-uniform topography. The as-received aluminum alloy product (100) may include intermetallic particles (114) (e.g., second phase particles) at least proximate to the surface oxide layer (102) (only one intermetallic particle is shown in FIG. 1). The intermetallic particles (114) may include, for example, Cu-containing intermetallic particles. The mixed oxide layer (112) may be on at least a portion of the intermetallic particles (114) and may include a mixture of magnesium oxide and aluminum oxide.

[0005] After receiving (302), at least a portion of the intermetallic particles (114) are exfoliated (304) to produce an exfoliated 7xxx aluminum alloy product (200) having an exfoliated portion (202) surrounded by a non-exfoliated portion (216). The exfoliating step (304) may be controlled (530) to avoid melting of the substrate (106). The exfoliating step (304) may include directing (504) an energy source at the surface oxide layer (102) to exfoliate (304) at least a portion of the intermetallic particles (114) (e.g., by controlling (530) the radiation conditions of the energy source).

[0006] In one embodiment, the receiving step (302) may also include a conditioning step (410). The conditioning step (410) may include a cleaning step (412) that includes contacting (e.g., wiping) the as-received 7xxx aluminum alloy product (100) with a suitable solvent (e.g., an organic solvent such as acetone or hexane). This cleaning step (412) facilitates the removal of debris (e.g., lubricants, oils, dirt) and other matter on the surface of the as-received 7xxx aluminum alloy product that may interfere with the subsequent stripping step (304).

[0007] The adjusting step (410) may also include a positioning step (418). The positioning step (418) may include positioning an energy source (e.g., laser (116)) above the surface oxidation layer (102) of the as-received 7xxx aluminum alloy product (100) for the subsequent stripping step (304). In one embodiment, the laser (116) may include a mounting for attaching the optics of the laser (116) to a robotic device (218) for process automation purposes. In this embodiment, the positioning step (418) may also include positioning the laser (116) above the surface oxidation layer (102) using the robotic device (218). In another embodiment, the positioning step (418) may further include positioning the as-received 7xxx aluminum alloy product (100) below the energy source (e.g., laser (116)) instead of or in addition to positioning the energy source above the surface oxidation layer (102). For example, without limitation, methods (300), (400) and (500) may be implemented, at least in part, as an automated process in which the as-received 7xxx aluminum alloy product (100) (e.g., sheet product) proceeds continuously through the receiving step (302) and the peeling step (304) and any intervening steps.

[0008] In one embodiment, the ablation step (302) may also include directing (504) a pulsed laser beam (208), such as a Q-switched diode-pumped solid-state (e.g., Nd:YAG) laser (116). In one embodiment, the pulsed laser (116) may operate at an average power of 300 W, and the pulsed laser (116) may direct (504) a laser beam (208) pulse up to 50 mm wide and up to 0.89 mm in diameter from a focal distance of 6-10 inches (approximately 15.2-25.4 centimeters) at (e.g., at a focal point proximate to) the surface oxide layer (102) with a maximum power of 230 kW per pulse. Other lasers and / or laser parameters may be used. The type of one or more pulsed lasers (116) may be adjusted (e.g., during the controlling step (530)) to achieve a desired effect during the directing step (504), as described below. In one embodiment, the pulsed laser (116) can direct (504) the laser beam (208) pulses at the surface oxide layer (102) at a pulse frequency of 15-40 kHz for a duration of 25-67 μsec. In another embodiment, the pulsed laser (116) can direct (504) the laser beam (208) pulses at the surface oxide layer (102) at a pulse frequency of 25 kHz for a duration of 40 μsec. In one embodiment, the pulsed laser (116) can direct (504) the laser beam (208) pulses at the surface oxide layer (102) with a pulse duration of 80-200 ns.

[0009] The ablation step (304) may further include directing (504) an energy source (e.g., laser (116)) at the surface oxide layer (102) to volatilize (502) at least a portion of the intermetallic particles (114) into a vapor (206), thereby creating a misaligned / fractured mixed oxide layer (212) and a plurality of ablation voids (214) (e.g., ablation pits) proximate the surface oxide layer (102). The directing step (504) may also include volatilizing (502) the intermetallic particles (114) by controlling (530) the radiation conditions of the energy source. The controlling step (530) may further include determining and controlling the operating parameters and / or settings of the laser (116) to achieve the desired volatilization (502) of the intermetallic particles (114), for example by inducing requisite heating conditions (e.g., temperature and / or heating rate) for the intermetallic particles (114) proximate to the surface oxide layer (102). These operating settings and / or parameters of the laser (116) may include at least one of the scan speed (e.g., feet / second), pulse frequency, pulse duration, average power, peak pulse power, beam width, beam diameter, hatch spacing (interscan distance), and focal length to the surface oxide layer (102).

[0010] In one embodiment, the directing step (504) and / or the volatilizing step (502) may include partially detaching (304) and / or partially volatilizing (502) one or more agglomerates of intermetallic particles (114) (e.g., where the intermetallic particles (114) have a size significantly larger than other intermetallic particles (114) of the as-received 7xxx aluminum alloy product (100)). In another embodiment, the directing step (504) and / or the volatilizing step (502) may include completely detaching (304) and / or completely volatilizing (502) an entire agglomerate of one or more intermetallic particles (114). In yet another embodiment, the directing step (504) and / or the volatilizing step (502) may include completely detaching (304) and / or completely volatilizing (502) all agglomerates of intermetallic particles (114) that are subject to energy absorption from an energy source (e.g., laser (116)). The directing step (504) and / or the volatilizing step (502) may also include displacing / breaking (506) at least a portion of the mixed oxide layer (112) on at least a portion of the intermetallic particles (114), thereby exposing exfoliated voids (214) to the exterior (220) of the exfoliated 7xxx aluminum alloy product (200).

[0011] The stripping step (304) may further include a removing step (522). The removing step (522) may include transporting the vapors (206), particulate matter, debris, and / or other by-products of the stripping step (304) distal to the stripped portion (202) and / or non-stripped portion (216) of the stripped 7xxx aluminum alloy product (200). These by-products may result from the effect of the laser (116) treatment on the surface oxide layer (102), the intermetallic particles (114), and / or the mixed oxide layer (112). In one embodiment, the removing step (522) may include a suction step (524). The suction step (524) may include suctioning the by-products of the stripping step (304), for example, using a vacuum pump (222) positioned proximate to the laser (116).

[0012] In another embodiment, the removing step (522) may include a blowing step (526). The blowing step (526) may include positioning a blower (224), for example, proximate to the laser (116), to blow (526) air, nitrogen, or other gas toward the exfoliated portion (202) and / or unexfoliated portion (216) to facilitate carrying the by-products of the stripping step (304) distal to the exfoliated portion (202) and / or unexfoliated portion (216) of the exfoliated 7xxx aluminum alloy product (200). With respect to the removing step (522), the blowing step (526) may be performed instead of or in addition to the suction step (524).

[0013] In one embodiment, the removing step (522) may be performed simultaneously with the directing step (504). In another embodiment, instead of or in addition to being performed simultaneously with the directing step (504), the removing step (522) may be performed after the directing step (504). In yet another embodiment, instead of or in addition to the sucking step (524) and / or blowing step (526), ​​the removing step (522) may be performed by rinsing the stripped 7xxx aluminum alloy article (200) with water (e.g., deionized water) and / or other suitable cleaning / rinsing agent.

[0014] In one embodiment, the surface oxide layer (102) of the as-received 7xxx aluminum alloy product may include an aluminum oxide sublayer (108) overlying the substrate (106). In another embodiment, the surface oxide layer (102) may also include a magnesium oxide sublayer (110) overlying the aluminum oxide sublayer (108). The stripping step (304) may also include maintaining (508) the surface oxide layer (102) at the as-received thickness (104). In one embodiment, the stripping step (304) may leave a stripped thickness (204) of the surface oxide layer (102) that is, at least on average, substantially equal to the as-received thickness (104). In another embodiment, the stripping step (304) may reduce the stripped thickness (204) of the surface oxide layer (102) as compared to the as-received thickness (104). In one embodiment, the stripped thickness (204) of the surface oxide layer (102) is about 5-60 nm. In another embodiment, the exfoliated thickness (204) of the surface oxide layer (102) is about 20-60 nm (e.g., an exfoliated 7xxx aluminum alloy product (200) in a W-, F-, or T-temper). In yet another embodiment, the exfoliated thickness (204) of the surface oxide layer (102) is about 5-20 nm (e.g., an exfoliated 7xxx aluminum alloy product (200) in a F-temper). In another embodiment, the exfoliated thickness (204) of the surface oxide layer (102) is ≦200 nm.

[0015] The stripping step (304) may also include maintaining (528) the overall composition / concentration of at least one of the constituent elements of the surface oxide layer (102) at the as-received element composition. The maintaining step (528) may include maintaining (528) the Mg composition of the surface oxide layer (102) at the as-received Mg composition (e.g., of the magnesium oxide sublayer (110)). In one embodiment, the stripping step (304) may result in the Mg composition of the stripped surface oxide layer (102) being maintained (528) substantially equal, at least on average, to the as-received Mg composition of the surface oxide layer (102). In another embodiment, the Mg composition of the stripped surface oxide layer (102) is maintained (528) close to the as-received composition of the 7xxx aluminum alloy product (100) (e.g., typically 20-45 atom % Mg).

[0016] In one embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg10 atom% (528). In another embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg12 atom% (528). In yet another embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg14 atom% (528). In another embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg16 atom% (528). In yet another embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg18 atom% (528). In another embodiment, the Mg composition after stripping of the surface oxide layer (102) is maintained at ≧Mg20 atom% (528).

[0017] The exfoliating step (304) may further include exfoliating (204) at least a portion of the intermetallic particles (114) without melting the substrate (106) of the exfoliated 7xxx aluminum alloy product (200). In one embodiment, an interface (118) may exist between the substrate (106) and the surface oxide layer (102). The substrate (206) may be aluminum alloy metal proximate the interface (118) and may generally be more reflective to the energy source radiation (e.g., laser beam (206) of laser (116)) compared to the intermetallic particles (114). The intermetallic particles (114), in contrast, may be less reflective to the energy source radiation and therefore may absorb more energy from the radiation (e.g., laser beam (206) of laser (116)) compared to the interface (118). The surface oxide layer (102) may be more transparent to the energy source radiation as compared to the intermetallic particles (114) and the substrate (106).

[0018] The stripping step (304) may also include selectively stripping (534) at least a portion of the intermetallic particles (114). The selectively stripping step (534) may utilize determining (432) the different properties, elemental compositions, and / or physical / chemical behaviors (e.g., relative thermal conductivities, relative thermal expansions, achievable peak temperatures, inducible heating rates and / or subsequent cooling rates during and / or after exposure to the radiation of the energy source) of the surface oxide layer (102) proximate the interface (118), the intermetallic particles (114), and the substrate (206). In one embodiment, the determining step (432) may be performed prior to the receiving step (302) and the stripping step (304). In another embodiment, the determining step (432) may be performed after the receiving step (302) and prior to the stripping step (304). The determining (432) and / or controlling (530) may thereby facilitate selectively exfoliating (534) at least a portion of the inter-metallic particles (114) without melting the substrate (206).

[0019] The exfoliating step (304) may further include selectively exfoliating (534) at least a portion of the intermetallic particles (114) in a surface grain structure of the substrate (106) (e.g., unexfoliated portion (216)) of the exfoliated (200) 7xxx aluminum alloy product, at least on average, compared to as-received (100), in the absence of any induced alterations. The determining step (432) and / or controlling step (530) may also thereby facilitate selectively exfoliating (534) at least a portion of the intermetallic particles (114) without causing any appreciable changes in the overall grain structure of the unexfoliated portion (216).

[0020] The exfoliating step (304) may further include selectively exfoliating (534) at least a portion of the intermetallic particles (114) to, at least on average, the overall roughness of the surface of the exfoliated (200) 7xxx aluminum alloy product (e.g., the unexfoliated portion (216)) compared to the as-received (100) in the absence of an induced change. The determining step (432) and / or controlling step (530) may also facilitate selectively exfoliating (534) at least a portion of the intermetallic particles (114) without causing an appreciable change in the overall roughness of the unexfoliated portion (216).

[0021] The method (500) may also include locating (536) the intermetallic particles (114) prior to selectively peeling (534) them. In one embodiment, the locating step (536) may include determining the location of the intermetallic particles (114) proximate the interface (118) of the as-received 7xxx aluminum alloy product (100). In one embodiment, one or more analytical techniques may be used on the sample of the as-received 7xxx aluminum alloy product (100) to, for example, determine the average distribution of the intermetallic particles (114) proximate the interface (118). For example, the average number of intermetallic particles (114) per unit area of ​​the surface of the as-received 7xxx aluminum alloy product (100) that is to be selectively peeled (534) may be determined using one or more analytical techniques. Such determinations may then be used in the controlling step (530), for example, by informing the selection of values ​​of operating parameters and / or settings (e.g., scan speed, focal position location for the directing step (504), beam diameter, beam width, etc.) of the laser (116) and / or robotic device (420) to selectively ablate (534) the located intermetallic particles (114). An analytical determination, such as the average number of intermetallic particles (114) per unit area of ​​a sample of the as-received 7xxx aluminum alloy product (100), may be applied to respective values ​​selected for the controlling step (530) for a plurality of units of the as-received 7xxx aluminum alloy product (100). For example, but not limited to, the determined average number of intermetallic particles (114) per unit area may inform the selection of one or more values ​​of operating parameters and / or settings of the laser (116) and / or robotic device (420) used throughout an automated and / or mass production process.

[0022] In one embodiment, the intermetallic particles (114) may define a pre-exfoliation volume in the as-received 7xxx aluminum alloy product (100). The exfoliating step (304) may further include creating at least some exfoliation voids or exfoliation pits (214) having a larger exfoliation void volume than the pre-exfoliation volume of the intermetallic particles (114). In one embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume of the intermetallic particles is >1:1. In another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >2:1. In yet another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >3:1. In another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >4:1. In yet another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >5:1. In another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >6:1. In yet another embodiment, the ratio of the exfoliation void volume to the pre-exfoliation volume is >7:1. In another embodiment, the ratio of the ablation void volume to the pre-ablation volume is >8: 1. In yet another embodiment, the ratio of the ablation void volume to the pre-ablation volume is >9: 1. In yet another embodiment, the ratio of the ablation void volume to the pre-ablation volume is >10: 1.

[0023] As discussed above, the delamination of copper-containing intermetallic particles may facilitate the production of 7xxx aluminum alloy products that can successfully pass appropriate adhesive bond tests. Without being bound to any particular theory, it is believed that the laser delamination of copper-containing intermetallic particles near or on the surface removes such particles without redepositing the copper contained in the copper-containing intermetallic particles on the aluminum alloy surface (e.g., by electroplating). Conventional chemical etching methods can remove copper-containing intermetallic particles (e.g., by dissolving), but such chemical etching methods may leave copper ions in solution, which may result in copper being redeposited (e.g., by electroplating) on ​​the aluminum alloy surface, resulting in copper enrichment. Copper enrichment from chemical etching may be due to selective oxidation / dissolution during chemical etching. Chemical etching may also lead to the formation of copper particles near or on the surface, which may be detrimental to subsequent functionalization processes. The new methods disclosed herein volatilize the intermetallic particles, generally preventing copper redeposition (e.g., by plating / electroplating). Thus, the multiple exfoliation voids (e.g., exfoliation pits) created by the new methods disclosed herein may leave exfoliation voids generally free of copper. The lack of copper in these exfoliation voids may facilitate the creation of a functionalization layer, and there is no need to remove the surface oxide layer of the 7xxx aluminum alloy product. The absence of copper particles on the surface may facilitate the creation of a functionalization layer, and there is no need to remove the surface oxide layer of the 7xxx aluminum alloy product.

[0024] The new 7xxx aluminum alloy products described herein have a high exfoliation pit density (e.g., at least 100 exfoliation pits / mm 2 ), the portions having a high exfoliation pit density are generally those that have been exposed to the energy source (e.g., laser). The portions that have not been exposed to the energy source (i.e., not exfoliated) may have a low exfoliation pit density (e.g., less than 100 exfoliation pits / mm 2In one embodiment, the 7xxx aluminum alloy product comprises at least 100 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In another embodiment, the 7xxx aluminum alloy product comprises at least 300 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In yet another embodiment, the 7xxx aluminum alloy product comprises at least 600 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In another embodiment, the 7xxx aluminum alloy product comprises at least 900 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In yet another embodiment, the 7xxx aluminum alloy product comprises at least 1200 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In another embodiment, the 7xxx aluminum alloy product comprises at least 1500 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In yet another embodiment, the 7xxx aluminum alloy product comprises at least 1800 exfoliation pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In another embodiment, the 7xxx aluminum alloy product comprises at least 2000 spalling pits per square mm of the exfoliated surface of the 7xxx aluminum alloy product. In one embodiment, the exfoliated surface is an exterior surface (i.e., the entire surface is spalled). In another embodiment, the exfoliated surface is one or more spalled zones (e.g., portions of the surface).

[0025] The intermetallic particles (114) of the as-received 7xxx aluminum alloy product (100) may include, for example, constituent particles and / or dispersoids. The intermetallic particles are generally at least 200 nanometers in size on average. The intermetallic particles may be located proximate to the interface (118) of the as-received 7xxx aluminum alloy product (100). The as-received 7xxx aluminum alloy product (100) may include other intermetallic particles (114), such as Fe-containing, Si-containing, and / or Mg-containing intermetallic particles, in addition to or instead of the Cu-containing intermetallic particles. The intermetallic particles may include, for example, but are not limited to, Al7Cu2Fe, Al2CuMg, and Al 12 At least some of the intermetallic particles (114) (e.g., those containing copper) may cause undesirable corrosion and / or adhesive bond problems. Thus, the exfoliating step (304) may also include improving the corrosion resistance (e.g., improving corrosion performance) of the exfoliated 7xxx aluminum alloy product (200). Thus, the exfoliating step (304) may include improving the adhesive bond performance of the exfoliated 7xxx aluminum alloy product (200), as described further below. In one embodiment, the exfoliating step (304) includes exfoliating at least some of the constituent particles but does not include a strengthening step. Such strengthening phases are typically less than 200 nm in size and less than 100 nm in size (e.g., about 50 nm in size on average) depending on the temper. In this regard, the 7xxx series aluminum alloys may include strengthening phases such as Mg2Si and Mg2Zn precipitates, among others. The 7xxx series aluminum alloys are, in particular, Al7Cu2Fe, Al2CuMg, and Al 12 The alloy may include constituent particles such as (Fe,Mn)Si. Thus, for a 7xxx series aluminum alloy, in one embodiment, the exfoliating (304) includes Al7Cu2Fe constituent particles, Al2CuMg constituent particles, and Al 12 This may include exfoliating one or more of the (Fe,Mn)3Si component particles, but does not include exfoliating at least one of the Mg2Si precipitates and the Mg2Zn precipitates.

[0026] Referring now to FIG. 6, the method (600) may include determining (602) at least one bond location associated with the exfoliated 7xxx aluminum alloy product (200). In one embodiment, determining (602) the at least one bond location may be performed prior to the receiving step (302) and prior to the exfoliating step (304). In another embodiment, the determining step (602) may be performed after the receiving step (302). The exfoliating step (304) may also include completing (604) the exfoliating step (304) for the at least one bond location, thereby creating the exfoliated portion (202). In one embodiment, the predetermined bond location may correspond to a preselected portion of the as-received 7xxx aluminum alloy product (100) that is exfoliated (304) during the exfoliating step (304) (e.g., a portion that is subsequently bonded to another material). In another embodiment, only those portions of the 7xxx aluminum alloy products (100 and / or 200) preselected to be adhesively bonded are debonded during the debonding step (304). Appropriate optics can be used to facilitate locating the predetermined locations for subsequent adhesive bonding.

[0027] 14a-14b, a schematic top view of an exterior surface of a 7xxx aluminum alloy product is shown (1400). The exterior surface (1400) includes a plurality of first zones (1410a, 1410b, 1410c, and 1410d) and a second zone (1420). As shown, the second zone (1420) has not been spalled, and thus the second zone is free of spalling pits. Conversely, the first zones (1410a, 1410b, 1410c, 1410d) have been spalled (e.g., by exposure to an energy source, etc.), and thus include a plurality of spalling pits. In this regard, FIG. 14b shows an enlarged view of a portion (1430) of the first zone (1410b) and a portion (1440) of the second zone (1420). As shown, the portion (1430) of the first zone (1410b) includes a plurality of spalling pits (1432). The illustrated portion (1430) of the first zone (1410b) is adjacent to a portion (1440) of the second zone (1420). The multiple first zones may be located in any suitable location and may be of any suitable size and / or shape. As such, the multiple first zones may be arranged in any suitable configuration relative to one another and the second zone. For example, the multiple first zones may be located in any suitable location, such as one or more of the top surface, the bottom surface, one or more edges, and / or one or more corners. The first zones may also be continuous across one or more surfaces of the 7xxx aluminum alloy product. For example, the first zone may include a first portion located on the top surface, a second portion located on the edges, and a third portion located on the bottom surface, where the first portion, the second portion, and the third portion are continuous with one another (i.e., not separated by the second zone). As such, the multiple first zones may be tailored according to the needs of the end product. For example, the multiple first zones may be associated with one or more predetermined bonding locations.

[0028] The plurality of first zones may generally achieve a depth not exceeding 10 micrometers. In one embodiment, one or more first zones achieve a depth not exceeding 7 micrometers. In another embodiment, one or more first zones achieve a depth not exceeding 5 micrometers. In yet another embodiment, one or more first zones achieve a depth not exceeding 4 micrometers. The exfoliation pits may achieve a depth not exceeding the depth of the exfoliation zone. Thus, in one embodiment, the plurality of exfoliation pits achieve an average depth not exceeding the depth of the one or more first zones.

[0029] Referring now to Figure 15, a schematic side view of a 7xxx aluminum alloy product (100) is shown. The 7xxx aluminum alloy product (100) includes an upper surface oxide layer (102) and a lower surface oxide layer (103) as described above. The lower surface oxide layer (103) is generally the same as the upper surface layer (102) prior to stripping. As shown, the 7xxx aluminum alloy product (100) includes an upper surface (150) and a lower surface (151). The upper surface (150) is associated with the upper surface oxide layer (102) and the lower surface (151) is associated with the lower surface oxide layer (103). As shown, the upper surface oxide layer (102) is disposed on an aluminum alloy substrate (106) and the lower surface oxide layer (103) is disposed on the bottom of the aluminum alloy substrate (106). Thus, the aluminum alloy substrate (106) is disposed between the upper surface (150) and the lower surface (151) and the respective surface oxide layers (102, 103). The surface oxide layers (102, 103) may have the surface oxide characteristics described in connection with Figures 1 and 2 above (e.g., MgO layer (110), AlO layer (108), intermetallic particles (114)). At least a portion of one or both of the surface oxide layers (102, 103) may be exfoliated. For example, a portion of the upper surface (150) may be exfoliated and the lower surface (151) may not be exfoliated. The surfaces may not be subjected to a stripping treatment and may be free of exfoliation pits. Thus, in one embodiment, the lower surface (151) is free of exfoliation pits. Additionally, the upper surface (150) and / or the lower surface (151) may include one or more stripped zones. Alternatively, the entire surface (150 or 151) is stripped (i.e., the entire surface is stripped).

[0030] I. Preparation of Functional Layer After the stripping step (304), a functional layer may be created on the stripped 7xxx aluminum alloy product (200). Prior to creating the functional layer, the stripped 7xxx aluminum alloy product (200) may be further prepared, for example, by rinsing the stripped 7xxx aluminum alloy product (200). The rinsing may include rinsing with water (e.g., deionized water) to remove debris and / or residual chemicals. In one embodiment, the rinsing step may grow additional aluminum oxide on the surface of the stripped 7xxx aluminum alloy product (200), which may nominally increase the thickness of the prepared surface oxide layer.

[0031] To create the functionalized layer, the exfoliated 7xxx aluminum alloy product (200) is typically exposed to a suitable chemical, such as an acid or base. Thus, the method (600) may also include a contacting step (606). The contacting step (606) may include contacting the exfoliated 7xxx aluminum alloy product (200) with a phosphorus-containing organic acid. In one embodiment, the contacting step (606) may include contacting the prepared 7xxx aluminum alloy product with any of the phosphorus-containing organic acids disclosed in U.S. Patent No. 6,167,609 to Marinelli et al., which is incorporated herein by reference. A layer of polymer adhesive may then be applied to the functionalized layer (e.g., for bonding to a metal support structure to form a vehicle assembly). The contacting step (606) may also include other chemical methods, such as using titanium with zirconium, to facilitate the production of the functionalized layer.

[0032] The phosphorus-containing organic acid typically interacts with the aluminum oxide in the surface oxide layer (102) to form a functionalized layer. The phosphorus-containing organic acid may be an organic phosphonic acid or an organic phosphinic acid. The organic acid is dissolved in water, methanol, or other suitable organic solvent to form a solution that is applied to the exfoliated 7xxx aluminum alloy product (200) by spraying, dipping, roll coating, or any combination thereof, thereby producing at least one pretreated portion into an exfoliated 7xxx aluminum alloy product (200). The pretreated portion is then rinsed with water after the acid treatment step.

[0033] The contacting step (606) may also include a step (608) of selectively contacting the exfoliated portion (202) with a phosphorus-containing organic acid to create a pre-treated portion of the exfoliated 7xxx aluminum alloy product (200). The selective contacting step (608) may include a limiting step (610). The limiting step (610) may include limiting contact between the unexfoliated portion (216) and the phosphorus-containing organic acid. In one embodiment, the limiting step (610) may include masking the unexfoliated portion (216) to prevent contact between the phosphorus-containing acid and the unexfoliated portion (216). In another embodiment, the limiting step (610) may include applying the phosphorus-containing organic acid as a gel formulation to facilitate contact only with the exfoliated portion (202).

[0034] The term “organophosphonic acid” refers to an acid having the formula R m [PO(OH)2] n where R is an organic group containing 1 to 30 carbon atoms, m is the number of organic groups and is about 1 to 10, and n is the number of phosphonic acid groups and is about 1 to 10. Some suitable organic phosphonic acids include vinyl phosphonic acid, methyl phosphonic acid, ethyl phosphonic acid, octyl phosphonic acid, and styrene phosphonic acid.

[0035] The term “organophosphinic acid” refers to an acid having the formula R m R' o [PO(OH)] nwhere R is an organic group containing 1 to 30 carbon atoms, R' is hydrogen or an organic group containing 1 to 30 carbon atoms, m is the number of R groups and is about 1 to 10, n is the number of phosphinic acid groups and is about 1 to 10, and o is the number of R' groups and is about 1 to 10. Some suitable organic phosphinic acids include phenylphosphinic acid and bis-(perfluoroheptyl)phosphinic acid.

[0036] In one embodiment, a vinylphosphonic acid surface treatment is used that essentially forms a monolayer of aluminum oxide on the surface layer. The coating area weight is about 15 mg / m 2 In one embodiment, the coating area weight is no more than about 3 mg / m 2 It is.

[0037] An advantage of these phosphorus-containing organic acids is that the pretreatment solutions contain less than about 1% chromium by weight, and are preferably substantially chromium-free, thus eliminating the environmental concerns associated with chromate conversion coating treatments.

[0038] In another embodiment, the functionalization layer is produced via a TiZr conversion coating process, where after laser stripping (and without the need for pickling / oxide removal), the applied portion of the aluminum alloy product is exposed to one or more solutions containing titanium and zirconium. In one embodiment, no oxide removal step is required, e.g., the method does not include a pickling step following laser stripping of the 7xxx aluminum alloy product. In one embodiment, a solution containing TiZr (e.g., a hydrogen hexachloride solution) is sprayed onto one or more laser stripped surfaces of the 7xxx aluminum alloy product, thereby forming a functionalization layer. In another embodiment, the laser stripped 7xxx aluminum alloy product is immersed in a solution containing TiZr. One known TiZr solution is GARDOBOND® X4591 from Chemetall (675 Central Avenue, New Provities, NJ 07974).

[0039] The functionalized exfoliated 7xxx aluminum alloy product (200) can then be cut to the desired size and shape and / or fabricated into a given configuration. Castings, extrusions and plate fabrications may also require sizing, for example, by machining, grinding or other milling processes. Molded assemblies made according to the present invention are suitable for many vehicle components, including automotive bodies, body-in-white components, doors, trunk decks, and hood lids.

[0040] The functionalized 7xxx aluminum alloy product can be bonded to a metal support structure using a polymer adhesive. Thus, the method (600) may further include selectively applying a bonding agent to the pre-treated portion of the exfoliated 7xxx aluminum alloy product (200). Thus, the method (600) may also include bonding the pre-treated portion of the exfoliated 7xxx aluminum alloy product (200) to another material with a bonding agent.

[0041] Methods (300), (400), (500) and / or (600) may be implemented in mass production processes, including, but not limited to, automotive and / or aerospace related manufacturing processes. In the manufacture of automotive parts, for example, it is often necessary to bond a functionalized 7xxx aluminum alloy material to an adjacent structural member. Bonding of a functionalized 7xxx aluminum alloy material can be accomplished in two steps. First, a layer of polymer adhesive is applied to a functionalized 7xxx aluminum alloy product, which is then pressed or pressed against another component (e.g., another functionalized 7xxx aluminum alloy product, a steel product, a 6xxx aluminum alloy product, a 5xxx aluminum alloy product, a carbon reinforced composite). The polymer adhesive may be an epoxy, polyurethane, or acrylic.

[0042] After the adhesive is applied, the parts may be spot welded, for example, at the bond areas of the applied adhesive. Spot welds may increase the peel strength of the assembly and facilitate handling during the time before the adhesive is fully cured. If necessary, the adhesive cure can be accelerated by heating the assembly to an elevated temperature. The assembly can then be passed through a zinc phosphate bath, dried, electrocoated, and subsequently painted with a suitable finish.

[0043] II. Aluminum alloys As discussed above, while various inventive aspects of the present invention have been illustrated using 7xxx aluminum alloys, the methods described herein may be used with any magnesium-containing aluminum alloy. A magnesium-containing aluminum alloy is an aluminum alloy having a sufficient amount of magnesium such that the MgO layer described above may be formed. As a non-limiting example, the magnesium-containing aluminum alloy includes 0.2-6 wt.% Mg. In one embodiment, the magnesium-containing aluminum alloy includes at least 0.5 wt.% Mg. Indeed, although the present disclosure has been described with respect to exfoliation of 7xxx aluminum alloy products and their intermetallic particles, it is anticipated that the exfoliation techniques described herein are applicable to other aluminum alloys having intermetallic particles available for exfoliation. Such other aluminum alloys may include one or more of 2xxx, 5xxx, 6xxx, and 8xxx (e.g., 8xxx aluminum alloys with high amounts of iron or lithium).

[0044] The magnesium-containing aluminum alloy may be in any form, such as a wrought product (e.g., rolled sheet or plate product, extrusion, forging). The magnesium-containing aluminum alloy product may alternatively be in the form of a shaped cast product (e.g., die cast). The magnesium-containing aluminum alloy product may alternatively be an additively manufactured product. As used herein, "additive manufacturing" means "a process of joining materials to make objects from 3D model data, usually by layering, as opposed to subtractive manufacturing methods," as defined in ASTM F2792-12a, entitled "Standard Terminology for Additively Manufacturing Technologies." The temper and aluminum alloy definitions provided herein (2xxx, 5xxx, 6xxx, 7xxx, 8xxx) are in accordance with ANSI H35.1(2009).

[0045] a.7xxx aluminum alloy The systems and methods disclosed herein may be applicable to 7xxx aluminum alloy products, such as those containing copper, which results in the formation of copper-containing intermetallic particles. In one method, the 7xxx aluminum alloy product includes 2-12 wt. % Zn, 1-3 wt. % Mg, and 1-3 wt. % Cu. In one embodiment, the 7xxx aluminum alloy product is made of Aluminum Association Teal.

[0023] The alloy may be one of 7009, 7010, 7012, 7014, 7016, 7116, 7032, 7033, 7034, 7036, 7136, 7037, 7040, 7140, 7042, 7049, 7149, 7249, 7349, 7449, 7050, 7150, 7055, 7155, 7255, 7056, 7060, 7064, 7065, 7068, 7168, 7075, 7175, 7475, 7178, 7278, 7081, 7181, 7085, 7185, 7090, 7093, 7095, 7099, or 7199 aluminum alloys as specified by USPTO Sheets (2015). In one embodiment, the 7xxx aluminum alloy is 7075, 7175, or 7475. In one embodiment, the 7xxx aluminum alloy is 7055, 7155, or 7225. In one embodiment, the 7xxx aluminum alloy is 7065. In one embodiment, the 7xxx aluminum alloy is 7085 or 7185. In one embodiment, the 7xxx aluminum alloy is 7050 or 7150. In one embodiment, the 7xxx aluminum alloy is 7040 or 7140. In one embodiment, the 7xxx aluminum alloy is 7081 or 7181. In one embodiment, the 7xxx aluminum alloy is 7178. Prior to stripping, the 7xxx aluminum alloy product may be F-, W-, or T-temper. Non-limiting examples of intermetallic particles that may be stripped in the 7xxx aluminum alloy product include, for example, Al7Cu2Fe, Al2CuMg, Al 12 Included among these are constituent particles (e.g., insoluble phases formed during solidification) such as (Fe,Mn)3Si and Al6(Fe,Mn) particles. Non-limiting examples of strengthening phases that may not be exfoliated are precipitates of Mg2Si and Mg2Zn, among others. l3Zr, Al 12 Mg2Cr, Al 12 (Fe,Mn)3Si, and Al 20 Cu2Mn3 dispersoids (e.g., particles formed during homogenization).

[0046] b.6xxx aluminum alloy The systems and methods disclosed herein are applicable to 6xxx aluminum alloy products. In one method, the 6xxx aluminum alloy product includes 0.2-2.0 wt.% Mg, 0.2-1.5 wt.% Si, and up to 1.0 wt.% Cu. In one embodiment, the 6xxx aluminum alloy product is one of 6111, 6013, 6022, 6x61, 6082, 6014, 6016, or 6063 aluminum alloy products, among others. Prior to stripping, the 6xxx aluminum alloy product may be F-temper, W-temper, or T-temper. Non-limiting examples of intermetallic particles that may be stripped in the 6xxx aluminum alloy product include, among others, Al, e.g., 12 (Fe,Mn,Cr)3Si and A l9 Non-limiting examples of strengthening phases that may not be exfoliated include Mg2Si and Q phase (Al5Cu2Mg8Si6) precipitates, among others.

[0047] c.5xxx aluminum alloy The systems and methods disclosed herein are applicable to 5xxx aluminum alloy products. In one method, the 5xxx aluminum alloy product is 0.5-6.0 wt.% Mg. In one embodiment, the 5xxx aluminum alloy product is one of 5754, 5182, 5052, 5050, 5083, 5086, 5154, 5252, 5254, 5454, 5456, 5457, 5652, 5657, 5349, 5005, or 5022 aluminum alloy products, among others. Prior to stripping, the 5xxx aluminum alloy product may be either O- or H-tempered. Non-limiting examples of intermetallic particles that may be stripped in the 5xxx aluminum alloy product include, for example, Al, among others. 12 (Fe,Mn)3Si is an example.

[0048] d.2xxx aluminum alloy The systems and methods disclosed herein are applicable to 2xxx aluminum alloy products. In one method, the 6xxx aluminum alloy product includes 0.5-7 wt.% Cu and 0.2-2.0 wt.% Mg. In one embodiment, the 2xxx aluminum alloy product is one of 2024, 2014, 2124, 2090, 2011, or 2219 aluminum alloy products, among others. Prior to stripping, the 2xxx aluminum alloy product may be F-temper, W-temper, or T-temper. Non-limiting examples of intermetallic particles that may be stripped in the 2xxx aluminum alloy product include, for example, Al7Cu2Fe, Al2Cu, Al2CuMg, Al, and Al, among others. 12 (Fe,Mn)3Si, Al6(Fe,Mn), and Al 20 Non-limiting examples of reinforcing phases that may not be exfoliated are Al2Cu, Al2CuMg, Al2CuLi, and Al3Li, among others. [Brief description of the drawings]

[0049] [Figure 1] FIG. 1 is a cross-sectional schematic diagram of an aluminum alloy product as received immediately prior to laser treatment (not to scale, for illustrative purposes only). [Diagram 2] FIG. 2 is a cross-sectional schematic diagram of a portion of an aluminum alloy product prepared by laser processing (not to scale, for illustrative purposes only). [Diagram 3] FIG. 3 is a flow chart illustrating one embodiment of a method for producing a conditioned aluminum alloy product in accordance with the present disclosure. [Figure 4] FIG. 4 is a flow chart illustrating one embodiment of the receiving process of FIG. [Diagram 5] FIG. 5 is a flow chart illustrating one embodiment of the stripping process of FIG. [Figure 6] FIG. 6 is a flow chart illustrating a further embodiment of the method of FIG. [Figure 7a]7a-7c are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7a), as laser treated at 25 kHz (FIG. 7b), and as functionalized (FIG. 7c). [Figure 7b] 7a-7c are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7a), as laser treated at 25 kHz (FIG. 7b), and as functionalized (FIG. 7c). [Figure 7c] 7a-7c are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7a), as laser treated at 25 kHz (FIG. 7b), and as functionalized (FIG. 7c). [Figure 7d] 7d-7f are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7d), as laser treated at 35 kHz (FIG. 7e), and as functionalized (FIG. 7f). [Figure 7e] 7d-7f are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7d), as laser treated at 35 kHz (FIG. 7e), and as functionalized (FIG. 7f). [Figure 7f] 7d-7f are XPS graphs of Example 1 illustrating the various concentrations and thicknesses of various 7xxx aluminum alloy products as received (FIG. 7d), as laser treated at 35 kHz (FIG. 7e), and as functionalized (FIG. 7f). [Figure 8a] 8a and 8b are SEM images of the alloy of Example 1 (magnification 80x) before (Figure 8a) and after (Figure 8b) laser treatment at 25 kHz. [Figure 8b] 8a and 8b are SEM images of the alloy of Example 1 (magnification 80x) before (Figure 8a) and after (Figure 8b) laser treatment at 25 kHz. [Figure 8c]8c and 8d are SEM images of the alloy of Example 1 (80x and 350x magnification, respectively) after laser treatment at 35 kHz (FIG. 8c) and 25 kHz (FIG. 8d). [Figure 8d] 8c and 8d are SEM images of the alloy of Example 1 (80x and 350x magnification, respectively) after laser treatment at 35 kHz (FIG. 8c) and 25 kHz (FIG. 8d). [Figure 8e] FIG. 8e is an enlarged view of FIG. 8d. [Figure 8f] FIG. 8f is a backscattered SEM image of the surface of a conventional (non-exfoliated) 7xxx aluminum alloy sheet product. [Figure 9a] 9a and 9b are SEM backscattering images of the alloy of Example 1 (80x magnification) before (FIG. 9a) and after (FIG. 9b) laser treatment at 25 kHz. [Figure 9b] 9a and 9b are SEM backscattering images of the alloy of Example 1 (80x magnification) before (FIG. 9a) and after (FIG. 9b) laser treatment at 25 kHz. [Figure 9c] FIG. 9c is an SEM backscattered image of the alloy of Example 1 (80x magnification) after laser treatment at 35 kHz. [Figure 10a] 10a and 10b are additional SEM backscattering images of the alloy of Example 1 (magnification 2000x) before (FIG. 10a) and after (FIG. 10b) laser treatment at 25 kHz. [Figure 10b] 10a and 10b are additional SEM backscattering images of the alloy of Example 1 (magnification 2000x) before (FIG. 10a) and after (FIG. 10b) laser treatment at 25 kHz. [Figure 11a] 11a and 11b are additional SEM backscattering images of the alloy of Example 1 (magnification 15000x) before (FIG. 11a) and after (FIG. 11b) laser treatment at 25 kHz. [Figure 11b]11a and 11b are additional SEM backscattering images of the alloy of Example 1 (magnification 15000x) before (FIG. 11a) and after (FIG. 11b) laser treatment at 25 kHz. [Figure 12a] 12a and 12b are SEM images of the cross section of the alloy of Example 1 (magnification 250x) before (FIG. 12a) and after (FIG. 12b) laser treatment at 25 kHz. [Figure 12b] 12a and 12b are SEM images of the cross section of the alloy of Example 1 (magnification 250x) before (FIG. 12a) and after (FIG. 12b) laser treatment at 25 kHz. [Figure 13a] 13a and 13b are additional SEM images of the cross section of the alloy of Example 1 (magnification 2000x) before (FIG. 13a) and after (FIG. 13b) laser treatment at 25 kHz, respectively. [Figure 13b] 13a and 13b are additional SEM images of the cross section of the alloy of Example 1 (magnification 2000x) before (FIG. 13a) and after (FIG. 13b) laser treatment at 25 kHz, respectively. [Figure 14a] FIG. 14a is a schematic top view of the outer surface of a 7xxx aluminum alloy product. [Figure 14b] FIG. 14b is an enlarged view of a portion of the first zone of FIG. 14a including a number of exfoliation pits. [Figure 15] FIG. 15 is a schematic side view of a 7xxx aluminum alloy product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] Example 1 7xxx aluminum alloy sheet products (Al-Zn-Mg-Cu type) were manufactured and processed to T76 temper (according to ANSI H35.1 requirements). Samples were taken from the 7xxx aluminum alloy sheets, after which the outer surfaces of the samples were cleaned with an organic solvent (e.g., hexane). The samples were then exposed to a Nd:YAG laser (Adapt Laser model CL300), a pulsed type laser unit with a rated power of 300 W. The pulse duration used to treat the samples was varied from 80 to 200 ns. A beam diameter of 390 μm was used for treatment. Some samples were exposed to a first pulse frequency condition (1) of 35 kHz, and other samples were exposed to a second pulse frequency condition (2) of 25 kHz.

[0051] After laser treatment, the samples were then treated with a phosphoric acid-containing organic acid at 150°F for 8 seconds to produce a functionalized layer thereon. The samples were then bonded in sequence and then subjected to an industry standard cyclic corrosion exposure test similar to ASTM D1002, whereby the samples were continuously subjected to a lap shear stress of 1080 psi to test the bond durability. The results are shown in Table 1 below.

[0052] [Table 1]

[0053] As shown, none of the samples in the Pulse Frequency 1 condition successfully completed the 45 cycles required to pass the test. However, three of the four samples processed in the Pulse Frequency 2 condition successfully completed the 45 cycles required to pass the test, with the sample failing after 34 cycles being higher than the number of cycles achieved by the Pulse Frequency 1 condition sample.

[0054] XPS (X-ray photoelectron spectroscopy) and SEM (scanning electron microscopy) were performed on some samples both before and after laser treatment, as well as after functionalization with phosphorus-containing organic acids. Figures 7a, 7b, and 7c are graphs plotting the XPS results for the first sample (A) of Example 1. Figure 7a plots the XPS results for sample A as received, prior to laser treatment at pulse frequency condition 2 (25 kHz) according to the protocol described above. Figure 7b plots the XPS results for sample A after laser treatment at pulse frequency condition 2. Figure 7c plots the XPS results for sample A after its laser-treated surface was contacted with a phosphorus-containing organic acid according to the procedure described above. In each of the graphs shown in Figures 7a-7c, the concentration of the surface component (atom%, y-axis) is plotted against distance (nm, x-axis). As shown in Figures 7a and 7b, the oxide layer (marked "O") is thicker than 10 nanometers (nm), the concentration of Mg is greater than 10 atom %, and the composition of the oxide layer is relatively unchanged both before and after laser treatment under condition 2.

[0055] 7d, 7e, and 7f are graphs plotting the XPS results of the second sample (B) of Example 1. FIG. 7d plots the XPS results of sample B as received before laser treatment at pulse frequency condition 1 (35 kHz) according to the protocol described above. FIG. 7e plots the XPS results of sample B after laser treatment at pulse frequency condition 1. FIG. 7f plots the XPS results of sample B after its laser-treated surface has been contacted with a phosphorus-containing organic acid according to the procedure described above. In each of the graphs shown in FIG. 7e and 7f, the concentration of the surface components (atom%, y-axis) is plotted against the distance (nm, x-axis). The results shown in FIG. 7c and FIG. 7d also show that the oxide layer components remain relatively unchanged, with the oxide layer being thicker than 10 nm and the concentration of Mg being greater than 10 atom% both before and after laser treatment at condition 1.

[0056] While the XPS results for samples treated under pulse frequency conditions 1 and 2 are substantially similar, analysis of the SEM micrographs shown in Figures 8-13 illustrates the superior bond durability performance of samples exposed to pulse frequency condition 2 compared to samples exposed to pulse frequency condition 1. Figures 8a and 8b are SEM images (80x magnification) of sample A of Example 1 before and after laser treatment under pulse frequency condition 2, respectively. Figure 8c is an SEM image (80x magnification) of sample B of Example 1 after laser treatment under pulse frequency condition 1. Figure 8d is an SEM image (350x magnification) of sample A of Example 1 after laser treatment under pulse frequency condition 2. Figures 9a and 9b are backscattered SEM images (80x magnification) of sample A before and after laser treatment under pulse frequency condition 2, respectively. Figure 9c is a backscattered SEM image (80x magnification) of sample B after laser treatment under pulse frequency condition 1. Figures 10a and 10b are backscattering images (magnification 2000x) of sample A before and after laser treatment, respectively. Figures 11a and 11b are backscattering images (magnification 15000x) of sample A before and after laser treatment, respectively.

[0057] 8a-8d and 9a-9c show that samples treated under both pulse frequency conditions 1 and 2 maintain substantially equivalent overall surface roughness both before and after laser treatment. Comparison of FIG. 10a to FIG. 10b and comparison of FIG. 11a to FIG. 11b show similar results for sample A exposed to pulse frequency condition 2. Notably, the surface oxide layers of samples A and B are unchanged by laser treatment under either pulse frequency condition 1 or pulse frequency condition 2. However, for sample A exposed to pulse frequency condition 2, the surface morphology of the sample is modified by delamination of intermetallic particles of the 7xxx aluminum alloy sheet product. Laser delamination of the intermetallic particles results in delamination pitting within the surface oxide layer, resulting in the pit-like voids (800) seen in FIGS. 8b, 8d, 9b, 10b, and 11b. In contrast, it is noted that the pit-like voids (800) are notably absent from the SEM images of the sample exposed to laser treatment pulse frequency condition 1, as shown in FIGS. 8c and 9c. In particular, FIG. 8d illustrates the roll grind lines (830).

[0058] For example, in FIG. 10a, the Fe-containing intermetallic particles are visible as bright particles up to about 2 μm in size. Also visible in FIGS. 10a and 11a are finer (e.g., smaller than those marked "Fe-containing") bright particles representing M-phase Mg(Zn,Al,Cu)2 particles and dispersoids. Additionally, in FIG. 10a, the dark particles represent Mg2Si or pores. In FIGS. 10b and 11b, the pit-like voids (800) on the surface indicate the location of the intermetallic particles that have been delaminated by the action of the laser treatment. The very fine pit-like voids (800) shown in FIGS. 10b and 11b correspond to the location of the M-phase particles Mg(Zn,Al,Cu)2 before delamination. As shown in FIG. 10b, the Mg2Si particles have also been delaminated.

[0059] 12a and 12b are SEM images (250x magnification) of a cross section of Sample A of Example 1 before and after laser treatment at pulse frequency condition 2, respectively. FIG. 13a is an SEM image (250x) of a longitudinal cut section of Sample A before laser treatment at pulse frequency condition 2. FIG. 13b is an SEM image (250x) of a cross section of Sample A after laser treatment at pulse frequency condition 2. Pit-like voids (800) are also seen in FIG. 12b. Without being bound by any theory, it is believed that the pitting facilitates sufficient penetration of the phosphorus-containing organic acid into the oxide during pretreatment, thereby facilitating sufficient adhesion of the polymer (e.g., adhesive bonding agent) to the oxide layer.

[0060] Furthermore, laser treatment under pulse frequency condition 2 selectively exfoliates the intermetallic particles without modifying the aluminum substrate underlying the surface oxide layer. This result can be seen by comparing FIG. 12a with FIG. 12b, where it is shown that the overall aluminum alloy grain structure near the surface is substantially unchanged after laser treatment, indicating that no melting of the aluminum substrate occurred as a result of laser treatment under pulse frequency condition 2. It was also observed that laser treatment of sample A under pulse frequency condition 1 exfoliates organic components (e.g., residual lubricant) from the surface resulting in a clean surface. Furthermore, comparing FIG. 13a with FIG. 13b further shows that laser treatment under pulse frequency condition 2 leaves behind pit-like voids (800), defining the volume in front of the exfoliated (e.g., volatilized) intermetallic particles (note the relative lack of second phase particles near the surface in FIG. 13b).

[0061] Laser delamination of intermetallic particles occurred under pulse frequency condition 2 but not condition 1, likely due to differences between the abilities of the intermetallic particles to absorb the energy of the laser beam at a rate sufficient to volatilize the intermetallic particles. In the case of Sample B processed under pulse frequency condition 1 (35 kHz) in Example 1, the Al7Cu2Fe-containing intermetallic particles of the 7xxx aluminum alloy sheet sample were not delaminated, whereas Sample A was delaminated when processed under pulse frequency condition 2 (25 kHz). Thus, provided that the laser beam exposure time was substantially constant, at least on average, between Samples A and B, laser treatment at 25 kHz facilitated volatilization of the intermetallic particles, whereas laser treatment at 35 kHz did not allow for delamination by volatilization.

[0062] The results of Example 1 indicate that acceptable bonding performance (e.g., achieving 45 cycles in the BDT test described above) can be achieved without appreciably altering, for example, the elemental composition (e.g., Mgatom%), the thickness of the oxide surface layer, and / or the roughness of the 7xxx aluminum alloy product. Furthermore, the differences observed in response to laser treatment between the two pulse frequency conditions described above provide for adjustment of the laser treatment parameters to delaminate intermetallic particles in various aluminum alloys. Delamination Pitting

[0063] The delamination pits created on the surface of the strip by the process of the present invention were counted in a secondary electron (SE) image of the surface. This mode typically highlights the topographical differences in the sample shown in FIG. 8d. The image was divided into 100×100 micrometer square sections, as illustrated by the grid in FIG. 8e. The number of delaminations in each of the six complete squares was counted and classified into three groups by size: (a) less than 5 micrometers, (b) less than 5 to 10 micrometers, and (c) 10-20 micrometers (for this particular sample, the delamination pits do not exceed 20 micrometers). As a result of the alignment of the constituent intermetallic particles in the rolling direction and the very non-uniform distribution shown in FIG. 8b, there was a substantial variation in the number and size of the delamination pits in each square. The resulting delamination pit counts were 80 pits below 5 micrometers, 30 pits in the size range of 5 to 10 micrometers, and 7 pits in the size range of 10 to 20 micrometers. Larger spallation pits are generally due to clusters of intermetallic particles. 28f, which corresponds to a pit density of 1950 pits / mm2, or a total of 117 pits across the area of ​​the exfoliation. Note that the exfoliation pits created by the present method show clearly visible rims on the larger exfoliation pits. Another difference is the presence of wrinkles (810) on the surface, which are likely sub-grain boundaries formed by the exfoliation process (e.g., wrinkles may form due to heating of the surface via an energy source). The presence of exfoliation pits substantially larger than the intermetallic grains of the untreated surface shown in FIG. 8f indicates that the process creates grooves around individual grains and clusters that are exfoliated to leave larger single pits. A typical untreated 7xxx metal surface is shown in Figure 8f (same magnification as Figure 8e) and in SEM in backscattered electron (BSE) mode. The image shows bright constituent grains containing Fe and Cu on a relatively smooth surface. The grains are typically smaller than 10 micrometers in diameter, aligned in the rolling direction, and often in the form of clusters. Exfoliation pits and wrinkles are generally absent.

[0064] Example 2 - Use of a Yb-YAG laser Several samples of 7xxx aluminum alloy products were delaminated using a Yb-YAG laser. The laser conditions were similar to those in Example 1. After laser delamination, the samples were examined by SEM. SEM analysis confirmed that the Yb-YAG laser properly delaminated the intermetallic particles from the surface, leaving behind the characteristic delamination pits described in Example 1. The samples showed no signs of surface melting.

[0065] After laser treatment, the samples were functionalized according to Example 1. The samples were then bonded in sequence and then subjected to an industry standard cyclic corrosion exposure test similar to ASTM D1002, whereby the samples were subjected to successive lap shear stresses of 1080 psi to test the bond durability. All samples successfully completed the required 45 cycles. The residual shear strength of the samples measured after completion of the exposure test was approximately 6000 psi.

[0066] Example 3 - Bonding of materials with laser treatment only Some of the laser-exfoliated samples of Example 2 were adhesively bonded after laser exfoliation, but without being functionalized, i.e., no functionalization layer was added to the sample. The samples were then subjected to the same industry-standard cyclic corrosion exposure test according to Examples 1 and 2. Nearly all of the 12 samples failed the test, many within 30 cycles. Thus, it appears that laser exfoliation alone does not facilitate the production of 7xxx aluminum alloy products suitable for adhesive bonding. A functionalization step / layer appears to be necessary.

[0067] Example 4 - Etching instead of functionalization Some of the laser-released samples of Example 2 were prepared for adhesive bonding by chemical etching with a dilute acid solution prior to bonding, but were not functionalized, i.e., no functionalization layer was added to the samples. The samples were then subjected to the same industry-standard cyclic corrosion exposure test according to Examples 1 and 2. All eight samples failed the test within 19 cycles. Thus, oxide etching is not a suitable substitute for a functionalization treatment.

[0068] While particular embodiments of the present disclosure have been described above for purposes of illustration, it will be apparent to those skilled in the art that many changes can be made to the details of the present disclosure without departing from the scope of the disclosure as defined in the appended claims.

Claims

1. 1. A magnesium-containing aluminum alloy sheet product comprising an upper surface and a lower surface, the upper surface includes a first zone and a second zone; the first zone comprises a plurality of exfoliation pits; the second zone is free of exfoliation pits; The average size of the pits is 20 μm or less; The magnesium-containing aluminum alloy sheet product comprises copper-containing intermetallic particles, and the plurality of exfoliation pits are copper-free.

2. 2. The magnesium-containing aluminum alloy sheet product of claim 1, the first zone is free of copper-containing intermetallic particles; 2. A magnesium-containing aluminum alloy sheet product, wherein the second zone comprises copper-containing intermetallic particles.

3. 1. A magnesium-containing aluminum alloy sheet product comprising an upper surface and a lower surface, the top surface of the magnesium-containing aluminum alloy sheet product comprises a surface oxide layer disposed on an aluminum alloy substrate; the surface oxidation layer includes an MgO portion, The surface oxide layer is Al 2 O 3 Including parts, The MgO portion is 2 O 3 at least partially disposed on the portion, the surface oxide layer is free of copper-containing intermetallic compound particles; the magnesium-containing aluminum alloy sheet product comprises copper-containing intermetallic particles; the magnesium-containing aluminum alloy sheet product comprises a plurality of exfoliation pits; the plurality of exfoliation pits are proximate to the surface oxide layer; the plurality of exfoliation pits are in the aluminum alloy substrate; the plurality of exfoliation pits do not contain copper; The magnesium-containing aluminum alloy sheet product, wherein the average size of the pits is 20 μm or less.

4. the top surface comprises a functionalized layer; the functionalization layer is disposed on the surface oxidation layer; The surface oxide layer is disposed on a substrate of a magnesium-containing aluminum alloy product, 4. The magnesium-containing aluminum alloy sheet product of claim 3, wherein a substrate of the magnesium-containing aluminum alloy product is disposed between an upper surface and a lower surface of the magnesium-containing aluminum alloy product.

5. The first zone is Mg 2 Si particles and Mg 2 2. The magnesium-containing aluminum alloy sheet product of claim 1, comprising at least one of Zn particles.

6. The magnesium-containing aluminum alloy sheet product, comprising a functionalized layer disposed at least partially on a surface oxide layer; the functionalized layer is formed from a phosphorus-containing organic acid; the exfoliation pits are present within the area of ​​the functionalized layer; The surface oxide layer is made of MgO and Al 2 O 3 and 2. The magnesium-containing aluminum alloy sheet product of claim 1, wherein the surface oxide layer is disposed on a substrate of the magnesium-containing aluminum alloy sheet product.

7. The magnesium-containing aluminum alloy sheet product, comprising a functionalized layer disposed at least partially on a surface oxide layer; the functionalized layer is formed from a phosphorus-containing organic acid; 2. The magnesium-containing aluminum alloy sheet product of claim 1, wherein said exfoliation pits are absent outside the area of ​​said functionalized layer.

8. 2. The magnesium-containing aluminum alloy sheet product of claim 1 , wherein said plurality of exfoliation pits achieve an average depth that is less than or equal to a depth of said first zone.

9. 2. The magnesium-containing aluminum alloy sheet product of claim 1, wherein the first zone has an exfoliation pit density, the exfoliation pit density being at least 100 exfoliation pits per square mm of the upper surface.

10. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 300 exfoliation pits per square mm of the upper surface.

11. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 600 exfoliation pits per square mm of the upper surface.

12. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 900 exfoliation pits per square mm of the upper surface.

13. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 1200 exfoliation pits per square mm of the upper surface.

14. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 1500 exfoliation pits per square mm of the upper surface.

15. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 1800 exfoliation pits per square mm of the upper surface.

16. 10. The magnesium-containing aluminum alloy sheet product of claim 9, wherein the exfoliation pit density is at least 2000 exfoliation pits per square mm of the upper surface.

Citation Information

Patent Citations

  • Production of bearing containing oil

    JP1987151588A

  • Surface treatment for corrosion resistance of aluminum

    US20150075756A1

  • Acid pretreatment for adhesive bonding of vehicle assemblies

    US6167609B1